Endoluminal shuntscope-guided ventricular catheter placement: Early experience - Agrawal, Vivek; Aher, Rajendra (Asian Journal of Neurosurgery, 2018)
Background: Placement of ventricular catheter (VC) in an optimal position is the most important factor in determining the outcome of shunt surgery. VC obstruction due to shunt tube placement in brain parenchyma, across the septa, tangled in the choroid plexuses and clogging of VC due to brain matter or other debris are common reasons resulting in shunt complete or partial dysfunction. To resolve these hurdles, many technical advancements have been made including navigation, stereotaxy, sonography, and ventriculoscope-guided VC placement. Objective: To report early experience, technique, and result of placing VC with shuntscope. Methods: We are publishing our experience of shuntscope-guided ventriculoperitoneal shunt in 9 cases done from June 2015 to April 2016. Shuntscope is a 1 mm outer diameter semi-rigid scope from Karl Storz with 10000 pixel of magnification. It has a fiber optic lens system with camera and light source attachment away from the scope to make it light weight and easily maneuverable. Results: In all cases, VC was placed in the ipsilateral frontal horn away from choroid plexuses, septae, or membranes. Septum pellucidum perforation and placement to opposite side of ventricle was identified with shunt scope assistance and corrected. Conclusion: Although our initial results are encouraging, larger case series would be helpful. Complications and cost due to shunt dysfunction can thus be reduced to a great extent with shuntscope.
Keywords: Endoluminal; shuntscope; ventricular catheter